MITM. WHAT IS IT, HOW TO PROTECT YOURSELF ANDIMPLEMENTATION FOR INSTRUCTIONAL USE - Abdinurova, N.; Akmyrza, D.; Mirash, A. (Journal of Emerging Technologies and Computing, 2021)
This is an attack in which a cybercriminal intercepts data while it is being transmitted. Man-in-the-Middle attacks are a common type of cybersecurity attack that allows attackers to eavesdrop on communications between two targets. This article discusses how people can protect themselves, what they need to know, and how an attacker performs a MITM attack using the open-source tools bettercap and net-creds in kali Linux. Buttercup is a network attack and monitoring program that can perform ARP spoofing and sniffing. Netcreds is a sniffing tool available by cloning on Github. This article attempts to implement this attack for instructional use.